The long-term effects of a randomized trial comparing aerobic interval versus continuous training in coronary artery disease patients: 1-year data from the SAINTEX-CAD study. (29th August 2020) - Pattyn, Nele; Vanhees, Luc; Cornelissen, Véronique A; Coeckelberghs, Ellen; De Maeyer, Catherine; Goetschalckx, Kaatje; Possemiers, Nadine; Wuyts, Kurt; Van Craenenbroeck, Emeline M; Beckers, Paul J
Abstract: Background: Aerobic interval training (AIT) and aerobic continuous training (ACT) both improve physical fitness (peak VO2 ) in coronary artery disease patients. However, little is known about the long-term effects of AIT and ACT on peak VO2 and exercise adherence. Design: This study is a randomized clinical multicenter trial. Methods: In total, 163 patients were assessed after 12 weeks of AIT or ACT and 12 months after their enrollment. Physical fitness and physical activity measures served as the primary outcomes, and peripheral endothelial function, cardiovascular risk factors and quality of life (QoL) served as the secondary outcomes. Results: Twenty-six patients dropped out during the intervention; 11 were lost during the follow-up period. Dropouts ( n = 37) consisted of more women ( p = 0.001) compared to completers ( n = 163). Physical fitness (VO2, heart rate and workload at peak and at thresholds) and physical activity (steps, active energy expenditure [kcal], physical activity duration [minutes]) were preserved at the 1-year follow-up ( p -time > 0.05) after both AIT and ACT ( p -interaction > 0.05). Forty percent of patients showed increased peak VO2, 52% showed increased active energy expenditure and 91.2% met the recommended levels of 150 minutes/week of moderate physical activity ( p -group > 0.05). Further, peripheral endothelial function, QoL and cardiovascular risk factors, except systolic blood pressure ( p -time < 0.05), remained stable ( p -time > 0.05) after both AIT and ACT ( p -interaction > 0.05). Conclusion: The short-term improvements of center-based AIT and ACT on physical fitness, physical activity, peripheral endothelial function, cardiovascular risk factors and QoL are sustained after a 1-year follow-up period. The majority of patients (>90%) met the recommended physical activity levels of 150 minutes/week.